Jurnal Pekerjaan Sosial: Kesejahteraan Keluarga Buruh Industri Genteng pada Masa Pandemi Covid-19 di Desa Burujul Wetan Kecamatan Jatiwangi Kabupaten Majalengka - Rifdah, Ishny Audhia (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2023)
This research aims to obtain an empirical description about: 1) respondent characteristic; 2) fulfillment of physical needs; 3) fulfillment of mental needs; 4) fulfillment of social needs; 5) fulfillment of economic needs; and 6) fulfillment of spiritual needs. This research used a quantitative method with descriptive survey design. The sample size was calculated using the Slovin formula with a 10% error rate. A total of 86 respondents were a tile industry workers in Burujul Wetan. Sampling technique applied in this research was area random sampling. The data collection technique used was questionnaire and documentary study. Validity test of measuring instrument used a face validity and correlation formula of product moment pearson by using SPSS v25. This research also used SPSS v25 to test the reliability of measuring instrument by looking at the value of cronbach’s alpha. Hereinafter, the result was analyzed by quantitative analysis descriptive. The results showed that the welfare level of the tile industry workers' families during the Covid-19 pandemic (40,70%) was unfulfilled, (45,35%) less fulfilled and (13,95%) fulfilled. Which can be seen that (52,23%) of physical aspect, (50%) of mental aspect, (41,86%) of social aspect, (60,47%) of economic aspect was unfulfilled and (53,49%) of spiritual aspect was fulfilled. Family needs unfulfilled due to tile industry workers' reduced incomes due to the company-working shift arrangement in response to the Covid-19 pandemic